Role of angiopoietin-2, endoglin, and placental growth factor in HIV-associated preeclampsia - Nokuzola Mbhele; Jagidesa Moodley; Thajasvarie Naicker (Taylor & Francis Group, 2017)
Objective: The factors angiopoeitin-2 (Ang-2), endoglin (Eng), and placental growth factor (PlGF) have been implicated in the pathophysiology of preeclampsia (PE). This study assessed their serum levels in HIV-negative and HIV-positive pregnant normotensive and pre-eclamptic women. Methods: Participants were recruited at the antenatal clinic, serum samples were evaluated using the Bioplex Human Cancer Biomarker (panel 2). Results: Ang-2 and Eng levels were higher, whilst PlGF levels were lower in the PE compared with the normotensive group. Pregnancy type had no significant effect on Ang-2 and showed a significant interaction with Eng (p < 0.0001) and PlGF (p = 0.0033). HIV status had no significant effect on angiopoeitin-2 (p = 0.4), Eng (p = 0.4), and PlGF (p = 0.7) but the levels were slightly higher in the HIV-negative cohort. Conclusions: This study demonstrates an elevation of Ang-2 and Eng in pre-eclamptic compared with normotensive pregnant women implicating their role in its pathogenesis.